Cohomological Rigidity of the Connected Sum of Three Real Projective Spaces - Choi, Suyoung; Vallée, Mathieu (Proceedings of the Steklov Institute of Mathematics, 2022)
Abstract: A real toric manifold (Formula presented.) is said to be cohomologically rigid over (Formula presented.) if every real toric manifold whose (Formula presented.)-cohomology ring is isomorphic to that of (Formula presented.) is actually diffeomorphic to (Formula presented.). Not all real toric manifolds are cohomologically rigid over (Formula presented.). In this paper, we prove that the connected sum of three real projective spaces is cohomologically rigid over (Formula presented.).
Keywords: cohomological rigidity; real toric manifold; real toric variety